Wide‐bandwidth multifrequency circularly polarized monopole antenna for wireless communication applications. Issue 3 (4th December 2018) - Bag, Biplab; Biswas, Priyabrata; Biswas, Sushanta; Sarkar, Partha Pratim
Abstract: In this article, wideband circularly polarized monopole antennas with multiresonating frequencies are presented for Bluetooth, WLAN, WiMAX, and X‐band applications. The designed antennas have dimensions of 50 × 35 × 1.6 mm 3 . Two different substrates (FR4‐epoxy and PTFE) are used for fabricating the antennas. The antennas consist of corner truncated I‐shaped and C‐shaped strips excited by a 50 Ω microstrip feed line. The parametric analyses are performed with the help of Ansoft HFSS V.11 EM simulator. Both antennas have been fabricated and measured. The measured percentage bandwidth of the antenna made by FR4 substrate is 31.32% (centered at 1.66 GHz), and 64.85% (centered at 5.69 GHz). The percentage bandwidth of antenna made by PTFE substrate is 20.57% (centered 2.43 GHz) and 68.74% (centered at 7.39 GHz). In addition to that, there exists 3 dB AR bandwidth for LHCP of about 1050 MHz for 5.2 GHz WLAN‐band. The reflection coefficient, radiation patterns, and the gains of both the antennas are studied in detail. It is found that the measured and simulated results are in good agreement.